The clinical utility and outcomes of microwave ablation for colorectal cancer liver metastases - Song, Pengyuan (Oncotarget, 2017)
In recent years, the microwave ablation (MWA) has been reported to play an important role in the treatment of patients with colorectal liver metastases (CRLM). In this work, 62 cases of patients who received MWA for liver metastases from colon or rectal cancer between Jan 2012 and Jan 2014 were enrolled in this trial. 28 underwent MWA, and 34 were treated with liver resection as control. Perioperative and 60 months of follow-up data were collected to analyze potential adverse effects, concurrent conditions and survival status. Here, we found there were no significant differences between both groups in the baseline level, including gender, size, number and pathological type (all p>0.05). In those patients, the mean hospitalization duration of patients with MWA is 5.9±0.9d, which is significantly different from control (11.8±6.9 d) (p<0.001). Little severe complication was observed in MWA group, while 26.5% (9/34) of patients developed severe complications (p=0.003). Besides, the mean hospitalization cost of patients with MWA was significantly less than that of control (p<0.000). Additionally, we found no statistically significant differences in disease-free survival (DFS) (p=0.156) or overall survival (OS) (p=0.580). In conclusion, MWA may be a safe, economical and competent way to treat inoperable CRLM patients, which has more advantages than liver resection in some degree.